2003
DOI: 10.1080/00207450390231446
|View full text |Cite
|
Sign up to set email alerts
|

Relearning of Locomotion in Injured Spinal Cord: New Directions for Rehabilitation Programs

Abstract: Locomotor activity-based rehabilitation programs seem to bring encouraging recovery to incomplete spinal cord injury paralytics. But in "complete" injuries recovery is long delayed and in small increments. Developmental and computer neural networks studies show that motor relearning requires the participation of redundant numbers of and activity-dependent competition of synapses among spinal interneurons. The present programs do not meet this prerequisite. They focus mainly on the mechanical (retraining) part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…To assess the effect of the walking conditions on physical exertion, VO 2 consumption in the steady-state period, walking distance, RPE (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and VAS (0-10) were used as outcomes. The walking distance covered was recorded every minute to obtain walking speed.…”
Section: Quantification and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of the walking conditions on physical exertion, VO 2 consumption in the steady-state period, walking distance, RPE (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and VAS (0-10) were used as outcomes. The walking distance covered was recorded every minute to obtain walking speed.…”
Section: Quantification and Statistical Analysesmentioning
confidence: 99%
“…As a consequence of the possible muscle atrophy, weakness, poor cardiovascular fitness prior to the stroke or as a result of the stroke, and hyper/hypotonic activity of the muscles contralateral to the side of the brain lesion [6] hemiparetic individuals have less endurance to accomplish activities of daily living [7][8][9][10]. Recent evidence indicated that, even after relatively short bouts of functional ambulation, individuals with stroke showed a significant decrease in their walking speed and endurance [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Second, in chronic SCI paralytics the cerebral cortical, and brain-stem locomotor maps have erroneously remapped themselves and gotten stubbornly stabilized; and therefore not contributing to any realistic "higher center" control. The author has recommended that if the first problem is taken care of, by inductive lability procedure (Krishnan, 2003a(Krishnan, , 2003b(Krishnan, , 2003c, then the second will take care of itself (Krishnan et al, 2001b). This article discusses in detail the process of reversing the incorrect cortical and sub-cortical maps with an objective of enhancing and hastening motor-sensory recovery in SCI.…”
Section: R V Krishnanmentioning
confidence: 97%
“…In the author's recent works (Krishnan, 2003b(Krishnan, , 2003c, he has discussed (1) the possible neural learning mechanisms that operate in the new rehabilitation programs that enabled the recovery; (2) the probable causes for the long delays (months/years) in the appearance of, and the relatively small increments in, the recovery process; and (3) prescribed measures to hasten and enhance recovery. He has cited two fundamental reasons for the delayed onset of recovery.…”
Section: R V Krishnanmentioning
confidence: 99%
See 1 more Smart Citation